Evaluating the confidence level of Traditional Chinese Medicine in nursing undergraduates at Chinese medical university† - Jia Rui-Min; Yang Zhi-Lan; Zhou Jing; Wu Xiao-Fen; Li Xuan-Xuan (Frontiers of Nursing, 2022)
To observe the confidence level prevailing with regard to the practice of Traditional Chinese Medicine (TCM) among undergraduate nursing students who have undertaken TCM courses at Shanxi Medical University.